Diapycnal mixing in the Brazil-Malvinas confluence front. (February 2023) - Roget, Elena; Pelegrí, Josep L.; Planella-Morato, Jesús; Puigdefàbregas, Joan; Emelianov, Mikhail; Vallès-Casanova, Ignasi; Orúe-Echevarria, Dorleta
Highlights: Microstructure data down to 400 m reveal the intensity of turbulence in a frontal region. Active turbulence was always present down to 400 m, often with high-dissipation patches. The geometric mean eddy diffusivity is 7.0 × 10–4 m 2 /s, increasing south of the front. Both vertical shear and double diffusion likely play a role in driving the enhaced mixing. Abstract: Diapycnal mixing in the Brazil-Malvinas Confluence Zone (BMC) is assessed on the basis of microstructure measurements done as part of an April 2017 cruise, which explored the mesoscalar and regional frontal dynamics. Sampling was done down to 400 m in 11 locations on both sides of the BMC, over the slope and in the abyssal waters. Turbulent scales, non-dimensional numbers, energy dissipation rates and diapycnal eddy diffusivities are calculated, which allow us to assess the state of the small-scale turbulence in the frontal region. Active turbulence was present at all depths and stations, with high-dissipation patches ranging from several metres to a few tens of metres. The frontal zone is characterized by high energy dissipation and eddy diffusivity. The geometric mean eddy diffusivity for all stations and the entire water column is 7.0 × 10 -4 m 2 s −1 . The mean values halve when only considering the more stratified seasonal thermocline, 3.8 × 10 -4 m 2 s −1, and are twice larger south than north of the BMC. High dissipation rates coincide with high vertical shear, possibly related to the convergence of the two intense currents and/or the generation of internal waves by the associated mesoscalar and submesoscalar features. The layered structures related to intruding filaments favor double diffusive convection and salt fingering. Near-bottom mixing at the stations on the continental slope is possible related to shear-driven Kelvin-Helmoltz instabilities.